Observations on Some Technical Terms in the *Vimuttimagga and their English Translations: An Examination of Jiā (夾) and Visayappavatti. (18th January 2016) - Kim, Kyungrae
Abstract : In the Chinese text of the *Vimuttimagga, namely the Jiĕtuō dào lùn (解脫道論), the word jiā (夾) is used as a technical abhidhamma term. It is used to refer to an initial cognitive activity through the five material sense organs. In the published English translation, the term is not understood clearly. There are similarities and differences between the two terms, jiā (夾)and visayappavatti. They are linked to similar doctrinal structures and technical terminology, especially the concept of bhavaṅga, which is a distinctive doctrine of Sri Lankan Theravāda. On the other hand, visayappavatti implies an initial cognitive activity by any of the six sense organs, while the term jiā refers to an initial cognitive activity only through the five material sense organs. A comparative study of the two terms proposes the following implications. Firstly, the text *Vimuttimagga is related to Sri Lankan Pāli abhidhamma because the orientation of the two terms is more than similar. Secondly, the text represents an early phase of the extant Pāli abhidhamma because the term jiā is less mature terminology than the term visayappavatti.